Snowbound with the rodeo star - Agler, Tanya (Harlequin heartwarming, 2023)
Will a surprising reunion...Warm their hearts?National Rodeo Champion Ty Darling is stunned when he runs into his ex, Sabrina MacGrath, in Violet Ridge, especially when he learns she's pregnant--with his baby! Now this commitment-wary rodeo cowboy has twelve days of Christmas to prove he's ready for a second chance at love. But being stranded together during a winter storm might just show them both the difference between being parents...and being a family.